PROSPECTS FOR OPTIMIZATION OF CUSTOMS PROCEDURES AT BORDER CUSTOMS POSTS USING INNOVATIVE METHODS (E Conference Zone, 2022)
This article discusses the prospects for optimizing customs procedures at border customs posts using innovative methods. In order to reform the customs administration, further improve and increase the efficiency of the customs authorities, the formation of a "digital customs", which is a logical continuation and development of "paperless and electronic customs", as well as accelerate the implementation of international norms and standards in national customs.